Does the “Environmental Kuznets Curve” Phenomenon Happening in High, Medium, and Low Income Countries? - Marselina, Marselina; Prasetyo, Tri Joko (International Journal of Energy Economics and Policy, 2023)
The most significant reduction in environmental quality is thought to have occurred in low-income countries, while low environmental degradation occurred in those high-income countries. Using the cluster purposive sampling technique, countries from 5 continents were examined to see if they had complete data and represented three categories. Seventy-eight countries were found to meet these requirements and were then used as research samples from 2015 to 2019. The Data Panel Regression technique was used to analyses the data. This study is expected to be able to produce policies in the form of a sustainable environmental management model that continues to support economic growth. This study proved that the Environmental Kuznets Curve (EKC) phenomenon applies from 2015 to 2019 in high-income countries, and population growth rates have a significant negative impact on Carbon Dioxide (CO2) emissions. This means that the more prosperous a country, the less the environmental degradation, while in low-income countries, carbon emissions increase when economic growth increases. In developing countries, as the population increases, environmental degradation increases, while in low-income countries the amount of carbon emissions is affected by economic growth and population. Some compensate and subsidies low-income countries which are able to care for their environment.